Pengaruh Current Ratio, Return on Asset, Struktur Aktiva dan Kepemilikan Manajerial terhadap Struktur Modal: (Studi Empiris pada Perusahaan yang Tergabung dalam Indeks LQ45 Non-Perbankan di Bursa Efek Indonesia Periode 2019-2023) - Jihan Nafisa Fitri; Slamet Mudjijah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the effect of Current Ratio, Return on Asset, Asset Structure and Managerial Ownership on Capital Structure. The population in this research is companies that are members of Index LQ45 listed on the Indonesia Stock Exchange in financial reports for the 2019-2023 period. The sampling technique in this research used a purposive sampling method and a sample of 18 companies was obtained. The analysis technique used is multiple linear regression analysis using IBM SPSS version 22. software. The results of this research show Current Ratio and Return on Asset have a negative and significant effect on Capital Structure, Asset Structure have a positive and significant effect on Capital Structure, while Managerial Ownership has no effect on Capital Structure.